Eutrophication: A new wine in an old bottle? - Le Moal, Morgane; Gascuel-Odoux, Chantal; Ménesguen, Alain; Souchon, Yves; Étrillard, Claire; Levain, Alix; Moatar, Florentina; Pannard, Alexandrine; Souchu, Philippe; Lefebvre, Alain; Pinay, Gilles (The Science of the total environment, 2019)
Eutrophication is one of the most common causes of water quality impairment of inland and marine waters. Its best-known manifestations are toxic cyanobacteria blooms in lakes and waterways and proliferations of green macro algae in coastal areas. The term eutrophication is used by both the scientific community and public policy-makers, and therefore has a myriad of definitions. The introduction by the public authorities of regulations to limit eutrophication is a source of tension and debate on the activities identified as contributing or having contributed decisively to these phenomena. Debates on the identification of the driving factors and risk levels of eutrophication, seeking to guide public policies, have led the ministries in charge of the environment and agriculture to ask for a joint scientific appraisal to be conducted on the subject. Four French research institutes were mandated to produce a critical scientific analysis on the latest knowledge of the causes, mechanisms, consequences and predictability of eutrophication phenomena. This paper provides the methodology and the main findings of this two years exercise involving 40 scientific experts. [Display omitted] •Eutrophication in the 70ies was related to point source pollution, mainly phosphorus.•Eutrophication is pervasive in many lakes, coastal areas and rivers of the world.•Diffuse nitrogen and phosphorus losses are now the main drivers of this new wave of eutrophication.•It is a wicked problem as a consequence of multiple, often cumulative actions other large spatio-temporal scales.•Solutions to tackle eutrophication need to address the entire land-sea continuum.